Global environmental governance, technology and politics the Anthropocene Gap - Galaz, Victor (Cheltenham Edward Elgar Pub, 2014)
Victor Galaz opens a new pathway, critically needed, yet breathtaking. In a thoughtful and inspirational manner, he takes on the challenge of how humanity is to navigate the unprecedented scale, speed and complexity of the Anthropocene. The focus is on the interplay between rapid nonlinear global environmental change and emerging technologies, like engineering the planet, tipping points, epidemic surprise or increased connectivity between financial markets, commodity markets, ecosystem services and underlying technologies. In a truly novel way, Galaz moves governance research to the very front of sustainability science and resilience thinking 'Global Environmental Governance, Technology and Politics' is indeed a groundbreaking contribution, highly recommended!'--Carl Folke, Stockholm University, Sweden.
Includes bibliographical references.
Keywords: Global environmental change